2017
DOI: 10.1101/159889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of venom composition across a complex life cycle

Abstract: Little is known about venom in young developmental stages of animals. The appearance of stinging cells in very early life stages of the sea anemone Nematostella vectensis suggests that toxins and venom are synthesized already in eggs, embryos and larvae of this species. Here we harness transcriptomic and biochemical tools as well as transgenesis to study venom production dynamics in Nematostella. We find that the venom composition and arsenal of toxin-producing cells change dramatically between developmental s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…For example, Underwood and Seymour () have documented distinct differences in tentacle venom protein profiles using 1D SDS–PAGE analyses between juvenile and mature Carukia barnesi medusae (the highly toxic Australian Irukandji jellyfish). Likewise, Columbus‐Shenkar et al () found also that venom composition changed dramatically between early developmental stages of the starlet sea anemone, Nematostella vectensis . Our research will further test the influence of how diet affects the expressed venome composition, by selective transcription and translation of component toxins, which will improve our understanding on how venom evolved in early cnidarian development.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Underwood and Seymour () have documented distinct differences in tentacle venom protein profiles using 1D SDS–PAGE analyses between juvenile and mature Carukia barnesi medusae (the highly toxic Australian Irukandji jellyfish). Likewise, Columbus‐Shenkar et al () found also that venom composition changed dramatically between early developmental stages of the starlet sea anemone, Nematostella vectensis . Our research will further test the influence of how diet affects the expressed venome composition, by selective transcription and translation of component toxins, which will improve our understanding on how venom evolved in early cnidarian development.…”
Section: Discussionmentioning
confidence: 96%